Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/ta.0000000000002132
|View full text |Cite|
|
Sign up to set email alerts
|

Management of blunt force bladder injuries: A practice management guideline from the Eastern Association for the Surgery of Trauma

Abstract: BACKGROUND The diagnostic evaluation and clinical management of bladder injuries caused by blunt force trauma are variable. We aim to formulate a practice management guideline using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. METHODS The working group, patient, intervention, comparator, outcome (PICO), formulated four questions regarding the following topics: (1) diagnostic evaluation based on patient basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Konservatif takip veya opere edilen hastaların en az 7-10 gün sondalarının tutulması önerilmektedir. Bizim çalışmamızda da ekstraperitoneal yaralanması olan tüm hastalar konservatif takip edilmiş olup intraperitoneal yaralanması olan hastalar opere edilmiştir (5,13,16,17).…”
Section: Discussionunclassified
“…Konservatif takip veya opere edilen hastaların en az 7-10 gün sondalarının tutulması önerilmektedir. Bizim çalışmamızda da ekstraperitoneal yaralanması olan tüm hastalar konservatif takip edilmiş olup intraperitoneal yaralanması olan hastalar opere edilmiştir (5,13,16,17).…”
Section: Discussionunclassified
“…3,16 Although definitive criteria are lacking, complex EBIs are usually defined as follows: concurrent rectal or vaginal injuries, open pelvic injuries, bladder neck injuries, and presence of bony spicules in the bladder lumen. 3,17…”
Section: Reviewmentioning
confidence: 99%
“…18,19,21,22 These recommendations mainly root in the concern for pelvic hardware contamination with urine and potential infectious complications when the EBI is not fixed. However, there are no prospective trials investigating this matter, and the evidence behind these recommendations are weak 3,17,18 and based upon low-quality data from small series. 23,24 Very few studies have directly looked at pelvic hardware infection after EBI, and although still controversial and subject to major selection biases, recent studies have shown mixed results comparing orthopedic complications in EBI patients who were managed nonoperatively compared to those who underwent surgical repair.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations